Radiograms Obtained during Anterior Cervical Decompression and Fusion Can Mislead Surgeons into Performing Surgery at the Wrong Level - Chikato Mannoji; Masao Koda; Takeo Furuya; Yuzuru Okamoto; Tamiyo Kon; Kazuhisa Takahashi; Masashi Yamazaki; Masazumi Murakami (Case Reports in Orthopedics)
A 68-year-old woman who suffered from C5 nerve palsy because of a C4-5 disc herniation was referred to our hospital. We conducted anterior cervical decompression and fusion (ACDF) at the C4-5 level. An intraoperative radiogram obtained after exposure of the vertebrae showed that the level at which we were going to perform surgery was exactly at the C4-5 level. After bone grafting and temporary plating, another radiogram was obtained to verify the correct placement of the plate and screws, and it appeared to show that the plate bridged the C5 and C6 vertebrae at the incorrect level. The surgeon was astonished and was about to begin decompression of the upper level. However, carefully double-checking the level with a C-arm image intensifier before additional decompression verified that the surgery was conducted correctly at C4-5. Cautiously double-checking the level of surgery with a C-arm image intensifier is recommended when intraoperative radiograms suggest surgery at the wrong level.